Polymorphism of SNP g.8398A>G at prolactin gene and its effect on Indonesian Holstein dairy cow’s milk performance and reproductive traits - Y. W. Setyorini; S. Sutopo; E. Kurnianto; S. Sutiyono (Diponegoro University, 2023)
The objective of this study was to identify the polymorphism of Single Nucleotide Polymorphism (SNP) g.8398A>G at the prolactin gene exon 4 in Indonesian Holstein dairy cows and its effect on milk production, milk quality, and reproductive traits. A total of 140 blood samples were investigated to detect polymorphism by PCR-RFLP method using the RsaI restriction enzyme. Sequencing was per-formed for confirmation of SNP mutation points. The phenotype data collected were milk production, milk quality, and reproductive traits. Data were analyzed using a t-test. The results showed that poly-morphism of SNP g.8398A>G at prolactin gene exon 4 was found in the study populations with AG and GG genotypes. Cows with the GG genotype indicated higher total milk yield and milk protein (P<0.05) than the AG genotype. Polymorphism was not associated with specific gravity, milk fat, milk lactose, total solid non-fat, and reproductive traits. SNP g.8398A>G at prolactin gene exon 4 showed potential as a genetic marker for selecting superior milk production traits.